BOOK REVIEW: LANGUAGE CURRICULUM DESIGN - Astri, Zul; Noer, Fhadli (LLT Journal: A Journal on Language and Language Teaching, 2023)
This book review analyzes "Language Curriculum Design" by I.S.P Nation and John Macalister, published in 2010 by Routledge. The review examines each chapter of the book in detail, highlighting the strengths and weaknesses of each section. The book provides a comprehensive and practical guide to language curriculum design, covering all aspects of the process from beginning to end. The authors present a variety of approaches to curriculum design, including negotiated syllabuses, adapting existing course books, and introducing change, and provide numerous examples, case studies, and sample materials to illustrate their points. The review notes that while the book is primarily focused on classroom-based language programs and may be less useful for other contexts, it draws on a wide range of research and theory in the field of language teaching and learning, making it a valuable resource for anyone interested in the subject. The review concludes that "Language Curriculum Design" is a useful and informative guide to curriculum design for language teachers and educators.